La cohérence institutionnelle d’une économie dépendante : formes de l’État et conflits redistributifs autour de la rente au Burkina Faso - Juliette Alenda; Pierre Robert (Revue de la Régulation)
Dependence, linked to integration with world capitalism, is a reality in Burkina Faso. It is based on a rentier economic regime, mainly agricultural. However, the long-run dynamics of Burkina Faso’s economy seem contrasted and lead us to question the overall coherence of an economic system driven by rent. For that, we study more particularly the form and the role of the State in Burkina Faso from a historical point of view. Starting from the regulationist approach, we develop an analytical grid, linking macroeconomic and institutional crises and regularities with the conflicting social relations that cross the country and lead to institutionalized compromises. We show that the State, in Upper Volta then in Burkina Faso, is the result of complex socio-political struggles and agreements between different groups, around the redistribution of the rent’s income. This economic system has been maintained since independence, as its external foundations, which are the monetary form and the form of international integration, have created relations of economic dependence. But it has also consolidated and developed through internal mechanisms, including the particular form of the State. We also highlight that, despite the difficulties encountered by the regulatory approach to study African countries, it remains relevant to understand the long-term dynamics on these territories, because it balances the political and economic logic.